2016
DOI: 10.1007/s12517-016-2737-7
|View full text |Cite
|
Sign up to set email alerts
|

Permian Calcareous algae from the Khachik Formation at the Ali Bashi Mountains, NW of Iran

Abstract: Micropaleontological investigations on Permian successions in the NW of Iran based on algae led to the determination of taxa belonging to some families such as Ungdarellaceae (Ungdarella uralica), Gymnocodiaceae (Gymnocodium bellerophontis and Permocalculus sp.), D a s y c l a d a l e s ( M i z z i a c f . M . y a b e i ) , a n d s o m e microproblematics (Vermiporella nipponica and Pseudovermiporella sodalica). These investigations are mainly focused on the Khachik Formation at the Ali Bashi Mountains. Accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Its area could be calculated by Equation (3): F I G U R E 6 Evolution of alatoconchids and the coeval environmental changes. The stratigraphic distribution is modified from Isozaki and Aljinovi c, 2009, according to the progress of international stratigraphic correlation (Lucas & Shen, 2018;Shen et al, 2019) and newly reported occurrences (Blodgett & Isozaki, 2013;Chen et al, 2018;Ghaderi, Taherpour Khalil Abad, Ashouri, & Korn, 2016) As the height of the crest decreases from a high peak to the periphery, its volume could be calculated as a cone, namely one-third of the product of the height and the base area. In this calculation, a small part would be double computed if H o ≠ H i (Figure 7e,f).…”
Section: Estimation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its area could be calculated by Equation (3): F I G U R E 6 Evolution of alatoconchids and the coeval environmental changes. The stratigraphic distribution is modified from Isozaki and Aljinovi c, 2009, according to the progress of international stratigraphic correlation (Lucas & Shen, 2018;Shen et al, 2019) and newly reported occurrences (Blodgett & Isozaki, 2013;Chen et al, 2018;Ghaderi, Taherpour Khalil Abad, Ashouri, & Korn, 2016) As the height of the crest decreases from a high peak to the periphery, its volume could be calculated as a cone, namely one-third of the product of the height and the base area. In this calculation, a small part would be double computed if H o ≠ H i (Figure 7e,f).…”
Section: Estimation Methodsmentioning
confidence: 99%
“…Evolution of alatoconchids and the coeval environmental changes. The stratigraphic distribution is modified from Isozaki and Aljinović, 2009, according to the progress of international stratigraphic correlation (Lucas & Shen, 2018; Shen et al, 2019) and newly reported occurrences (Blodgett & Isozaki, 2013; Chen et al, 2018; Ghaderi, Taherpour Khalil Abad, Ashouri, & Korn, 2016). Sakmar., Sakmarian; N ., Neoschwagerina ; s ., simplex ; c ., craticulifera ; m ., margaritae .…”
Section: An Overview On Alatoconchidaementioning
confidence: 99%
“…The occurrence of nodular chert in the lower part of the Formation is characteristic. The overlying Capitanian–early Wuchiapingian Khachik Formation (Ghaderi et al, 2016) consists of thin- and thick-bedded limestones passing upward into marly limestones and limestones with chert nodules interbedded with shales. The topmost unit of the Khachik Formation is characterized by dark-gray limestones, forming a unit named the Codonofusiella Limestone.…”
Section: Geological Settingmentioning
confidence: 99%
“…The topmost unit of the Khachik Formation is characterized by dark-gray limestones, forming a unit named the Codonofusiella Limestone. The Lopingian Julfa Formation (Julfa Beds sensu Stepanov et al, 1969) (Schobben et al, 2015; Ghaderi et al, 2016) is composed of nodular limestones and marly limestones with intercalations of gray to red shales. The Lopingian Ali Bashi Formation (Teichert et al, 1973; Schobben et al, 2015; Korn et al, 2016) comprises the unnamed shaly unit (Ghaderi et al, 2014) mostly characterized by red shales and the Paratirolites Limestone represented by red, nodular, marly limestones that are rich in ammonoids.…”
Section: Geological Settingmentioning
confidence: 99%
“…Studies of fossil dasycladaleans focus mainly on their morphology and taxonomy at the genus and species level (Johnson, 1961a; Pia, 1926), on their palaeoecology, biostratigraphic application, and palaeoenvironmental significance (Barattolo, 1991; Bucur, 1999; Granier & Deloffre, 1993; Johnson, 1961b). Considerable researches focusing on the depositional environments of the dasycladaleans in the Late Palaeozoic (Flügel, 1977; Ghaderi, Abad, Ashouri, & Korn, 2016; Kirkland & Chapman, 1990; Krainer, 1995; Krainer, Flügel, Vachard, & Joachimski, 2003; Samankassou, 1999), Mesozoic (Abate, Catalano, D'Argenio, Di Stefano, & Riccobono, 1977; Barattolo & Bigozzi, 1996; Bucur, Rashidi, & Senowbari‐Daryan, 2012; Bucur & Sasaran, 2005, 2012; Bucur, Schlagintweit, Rashidi, & Saberzadeh, 2016; Flügel, 1979; Henrich, 1984; Jamalian et al, 2011; Mircescu, Bucur, & Sasaran, 2014; Morin, Desrochers, & Beauchamp, 1994; Ruffer & Zamparelli, 1997; Senowbari‐Daryan, Zuhlke, Bechstadt, & Flugel, 1993), Cenozoic successions (Hanif et al, 2014; Humane, Chaurpagar, Humane, & Kundal, 2010; Kundal & Kundal, 2010), as well as in the present‐day (Ohba, Matsuda, Asami, & Iryu, 2017) have been performed, revealing that dasycladaleans were mainly distributed in lagoonal environments (Abate et al, 1977; Barattolo & Bigozzi, 1996; Flügel, 1979; Hanif et al, 2014; Humane et al, 2010; Jamalian et al, 2011; Ruffer & Zamparelli, 1997), with a lesser representation in platform margins (Bucur & Sasaran, 2012; Mircescu et al, 2014), reefs (Bao, Jiang, Wu, Ren, & Liu, 2016; Bucur & Sasaran, 2012; Ohba et al, 2017), and open platforms (Flügel, 1977).…”
Section: Introductionmentioning
confidence: 99%